2004
DOI: 10.1038/sj.bjc.6602251
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HER3, HER4 and their ligand heregulin-4 is associated with better survival in bladder cancer patients

Abstract: The epidermal growth factor system has been associated to prognosis in patients with bladder cancer based mainly on the expression of the epidermal growth factor (EGF) receptor 1 (EGFR) and HER2 and their activating ligands. Since limited information exists concerning the expression of other parts of the EGF system, we examined the expression of the receptors HER3 and HER4 and their activating ligands, the heregulins (HRGs), in bladder cancer patients. Biopsies from bladder cancer tumours were obtained from 88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
64
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 41 publications
8
64
0
Order By: Relevance
“…However, growing consensus has emerged about the role of HER4, and the few clinical studies carried out so far have suggested that its expression is associated with favourable prognosis (Thybusch-Bernhardt et al, 2001;Suo et al, 2002;Rotterud et al, 2005). We have shown that HER3 and HER4 expression correlated with a better prognosis in bladder cancer patients (Memon et al, 2004). More recent reports also suggest that unlike HER1 and HER2, expression of HER3 and HER4 was not found in more aggressive metastatic squamous cell carcinomas of the oral cavity (Ekberg et al, 2005).…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…However, growing consensus has emerged about the role of HER4, and the few clinical studies carried out so far have suggested that its expression is associated with favourable prognosis (Thybusch-Bernhardt et al, 2001;Suo et al, 2002;Rotterud et al, 2005). We have shown that HER3 and HER4 expression correlated with a better prognosis in bladder cancer patients (Memon et al, 2004). More recent reports also suggest that unlike HER1 and HER2, expression of HER3 and HER4 was not found in more aggressive metastatic squamous cell carcinomas of the oral cavity (Ekberg et al, 2005).…”
mentioning
confidence: 56%
“…HER3 and HER4 mRNA expressions have previously been determined on the same samples (Memon et al, 2004). HER1 was expressed in 96% (85 out of 88 Table 2 Correlation between combinations of HER1 and HER3/HER4 and clinicopathological parameters of bladder cancer…”
Section: Pattern Of Egf Family Receptor Expression and Correlation Wimentioning
confidence: 97%
See 3 more Smart Citations